Synthetic glycopolymers as modulators of protein aggregation: influence of chemical composition, topology and concentration - Madeira do Ó, João; Mastrotto, Francesca; Francini, Nora; Allen, Stephanie; van der Walle, Christopher; Stolnik, Snow; Mantovani, Giuseppe (Royal Society of Chemistry, 2018)
Novel drug excipients are required to achieve stable formulations of protein drug candidates. Synthetic glycopolymers have been shown in some cases to improve protein formulation stability, although their structure function relationship remains unknown. Here we report the synthesis of linear or 4-arm star glycopolymers with different molecular topology and chemical composition, with mannose, galactose, arabinose, N-acetyl glucosamine, lactose and trehalose pendant units - and investigate their modulation of conformational stability and aggregation propensity of a model monoclonal antibody (mAb1). Mono-and di-saccharides with free reducing ends are not frequently utilised as protein stabilisers, due to potential reactivity with a protein’s amine groups. In this study this was circumvented through the use of a stable acetal linker connecting the polymer backbone to the sugar pendant residues, which made the latter virtually non-reactive with amines. The general destabilisation the antibody was determined as anunfolding transition temperature (Tm) of CH2 and Fab structural domains, and aggregation temperature (Tagg). The most prominent effect of the glycopolymers on a temperature induced stress in a low concentration solutions was a decrease in Tm and Tagg, regardless of sugar composition or glycopolymer topology - in contrast to the stabilising effect of the corresponding mono- and di-saccharide constituents. The exceptions of linear-lactose and star-trehalose glycopolymers, which increased Tm of the mAb Fab region and Tagg, however, highlights a more complex structure-function relationship. Accelerated stability studies of the high concentrated mAb solutions (50 mg mL-1) revealed that the increased glycopolymer concentrations generally decreased the mAb stability, as judged by the amount of mAb1 ‘monomer’ molecules in solution, with star- and linear-trehalose glycopolymers further generating visible aggregates. Interestingly the latter effect could not have been predicted from the Tm or Tagg experiments conducted at a low concentration regime. Taken together, the data demonstrate a complex interplay of sugar chemistry and molecular topology of the synthetic glycopolymers on their modulation of protein conformational stability and aggregation propensity. Solution concentration was also an important parameter contributing to the stability modulation, and suggests that the stabilising properties of a sugar as the mono- or di-saccharide cannot be extrapolated to the corresponding glycopolymers.